Community Ecology and Biomonitoring in IRES - Stubbington, Rachel (2020)
Intermittent rivers and Ephemeral Streams (IRES) are river water bodies characterised by temporary flow. They are widespread across the EU and a significant proportion of them is expected to increase due to climate change scenarios and rising water demands. The purpose of this handbook is to help water managers to understand the natural processes prevailing in IRES and their importance for biodiversity and local communities in order to better manage them. Since it is widely accepted that these types of systems have been up until recently neglected, the transfer of knowledge from scientists to water managers is required for their proper ecological status assessment, and crucial for their protection and restoration. Therefore, this SMIRES handbook will also bring about a better understanding of IRES, and will provide for the provision of tools needed for managing them in the best possible way. Eight case studies, located in different countries, aim at illustrating different experiments of managing IRES where the knowledge previously presented in the handbook is needed and used. These experiments do not claim to be exemplary practices to be reproduced everywhere but instead give insights of what could be done, what should be strengthened and what should be avoided in specific contexts. The issues are various: restoration of habitats, reduction of erosion, flood prevention, mitigation of hydrological drought, raise of groundwater levels, etc. Among the lessons learned, all case studies insist on the importance of increasing people awareness about the ecosystem services associated with IRES and encourage local stakeholders to involve themselves in restoration projects of IRES. A specific attention to project monitoring is also pointed out to assess the outputs and to encourage other initiatives to be taken.